Effect of bariatric surgery on liver metabolism -studies using positron emission tomography - Immonen, Heidi (fi=Turun yliopisto|en=University of Turku|, 2019)
Obesity is a significant and increasing health challenge. Obesity is strongly associated with the incidence of type 2 diabetes (T2D). In obese individuals, liver insulin resistance is a major factor in the development and pathophysiology of T2D. Currently, bariatric surgery is the most effective therapy for morbidly obese patients. The aim of this thesis was to study the effects of surgery-induced weight loss on glucose and lipid metabolism in the liver, and to understand the beneficial effects of bariatric surgery on fatty liver, insulin resistance and T2D. Multimodality imaging by positron emission tomography (PET) combined with magnetic resonance imaging (MRI) and magnetic resonance spectroscopy (MRS) were utilized to study brain glucose uptake (BGU) and hepatic glucose uptake (HGU), hepatic fatty acid uptake, liver blood flow and liver fat content in morbidly obese patients (n=46) with and without T2D before and six-months after surgery (either sleeve gastrectomy (SG) or Roux-en-Y gastric bypass (RYGB)). The results were then compared to healthy subjects. Preoperatively, insulin-stimulated HGU was lower in obese patients before surgery as compared to the non-obese controls. HGU increased by 30-40% after surgery as compared to the preoperative situation. Postoperatively, liver fat and endogenous glucose production (EGP) were comparable to lean controls. Before surgery, the liver fatty acid uptake was increased in obese subjects as compared to lean controls and associated with body adiposity. Liver fatty acid uptake decreased after surgery but was still high compared to controls. Portal blood flow (per volume of tissue) was increased after surgery, but as the liver volume decreased along with the surgeryinduced weight loss, the whole organ blood flow was unchanged. A positive association between BGU and EGP during insulin stimulation was found in obese subjects and the association persisted after surgery. High BGU at baseline predicted a smaller improvement in fasting plasma glucose at a 2 and 3 year follow-up. The results of this study suggest that bariatric surgery, either SG and RYGB, is effective in improving hepatic glucose metabolism. The persistence of high fatty acid uptake, despite a normal fat content in the liver, suggests a change in the use of fatty acids from storage to oxidation after surgery. Accelerated portal blood flow may relate to improved liver metabolism after surgery. Moreover, these findings suggest the presence of a brain-liver axis in morbidly obese individuals. This axis might contribute to further deterioration of glucose homeostasis.

Lihavuusleikkauksen vaikutus maksan aineenvaihduntaan : tutkimuksia positroniemissiotomografiaa käyttäen Lihavuus on merkittävä ja paheneva terveysongelma. Tyypin 2 diabeteksen (T2D) ilmaantuvuus on yhteydessä lihavuuteen. Maksan insuliiniresistenssi vaikuttaa ratkaisevasti T2D:n kehittymiseen lihavilla henkilöillä. Lihavuusleikkaus on nykyisin tehokkain lihavuuden hoitokeino. Väitöskirjan tarkoitus oli tutkia lihavuusleikkauksen jälkeisen painonlaskun vaikutusta maksan glukoosi- ja rasva-aineenvaihduntaan ja ymmärtää lihavuusleikkauksen vaikutusta rasvamaksaan, insuliiniresistenssiin ja T2D:een. Positroniemissiotomografia (PET), magneettiresonanssi (MRI) ja magneettispektroskopia (MRS) -kuvantamisen avulla tutkittiin aivojen ja maksan glukoosin soluunottoa, maksan rasvahappojen soluunottoa, maksan verenkiertoa ja maksan kokoa ja rasvapitoisuutta lihavilla ennen lihavuusleikkausta ja kuusi kuukautta leikkauksen (joko mahalaukun kavennusleikkaus tai mahalaukun ohitusleikkaus) jälkeen. Tutkimuksessa käytettiin terveitä, normaalipainoisia verrokkiryhmänä. Ennen leikkausta maksan glukoosin soluunottokyky oli heikentynyt lihavilla ja se parani 30-40%:lla lihavuusleikkauksen jälkeen leikkausta edeltäneeseen tilanteeseen verrattuna. Leikkauksen jälkeen maksan rasvapitoisuus ja maksan glukoosin tuotanto vähenivät terveiden, normaalipainoisten verrokkien tasolle. Maksan rasvahappojen soluunotto oli lisääntynyt lihavilla ennen leikkausta ja se oli yhteydessä kehon rasvapitoisuuteen. Leikkauksen jälkeen rasvahappojen soluunotto väheni jonkin verran, mutta ei normaalistunut. Maksan porttilaskimon verenvirtaus (ml/min/ml) lisääntyi lihavuusleikkauksen jälkeen, mutta koska maksan koko pieneni leikkauksen jälkeen ei koko elimen verenvirtaus muuttunut. Lihavilla aivojen ja maksan glukoosin soluunotto olivat yhteydessä toisiinsa, ja yhteys säilyi lihavuusleikkauksen jälkeen. Leikkausta edeltänyt lisääntynyt aivojen glukoosin soluunotto ennusti vähäisempää paastoglukoosin laskua 2 ja 3 vuoden kuluttua leikkauksesta. Tutkimuksen perusteella lihavuusleikkaus parantaa tehokkaasti maksan aineenvaihduntaa. Vaikka rasvamaksa paranee leikkauksen jälkeen, pysyy maksan rasvahappojen soluunotto lisääntyneenä, mikä viittaa siihen, että rasvahapot käytetään energian tuotantoon sen sijaan että ne varastoitaisiin. Lisääntynyt porttilaskimon verenvirtaus saattaa olla yhteydessä parantuneeseen maksan aineenvaihduntaan leikkauksen jälkeen. Lisäksi tulokset viittaavat aivomaksa -akselin olemassaoloon. Sillä voi olla merkitystä elimistön glukoosiaineenvaihdunnan heikkenemisessä.